Evaluating Muscle Mass by Using Markers of Kidney Function: Development of the Sarcopenia Index - Kashani, Kianoush B; Frazee, Erin N; Kukrálová, Lucie; Sarvottam, Kumar; Herasevich, Vitaly; Young, Phillip M; Kashyap, Rahul; Lieske, John C (Critical care medicine, 2017)
OBJECTIVES: Sarcopenia is associated with a poor prognosis in the ICU. The purpose of this study was to describe a simple sarcopenia index using routinely available renal biomarkers and evaluate its association with muscle mass and patient outcomes. DESIGN: A retrospective cohort study. SETTING: A tertiary-care medical center. PATIENTS: High-risk adult ICU patients from October 2008 to December 2010. INTERVENTIONS: The gold standard for muscle mass was quantified with the paraspinal muscle surface area at the L4 vertebrae in the subset of individuals with an abdominal CT scan. Using Pearson's correlation coefficient, serum creatinine-to-serum cystatin C ratio was found to be the best performer in the estimation of muscle mass. The relationship between sarcopenia index and hospital and 90-day mortality, and the length of mechanical ventilation was evaluated. MEASUREMENTS AND MAIN RESULTS: Out of 226 enrolled patients, 123 (54%) were female, and 198 (87%) were white. Median (interquartile range) age, body mass index, and body surface area were 68 (57-77) years, 28 (24-34) kg/m, and 1.9 (1.7-2.2) m, respectively. The mean (± SD) Acute Physiology and Chronic Health Evaluation III was 70 (± 22). ICU, hospital, and 90-day mortality rates were 5%, 12%, and 20%, respectively. The correlation (r) between sarcopenia index and muscle mass was 0.62 and coefficient of determination (r) was 0.27 (p < 0.0001). After adjustment for Acute Physiology and Chronic Health Evaluation III, body surface area, and age, sarcopenia index was independently predictive of both hospital (p = 0.001) and 90-day mortality (p < 0.0001). Among the 131 patients on mechanical ventilator, the duration of mechanical ventilation was significantly lower on those with higher sarcopenia index (-1 d for each 10 unit of sarcopenia index [95% CI, -1.4 to -0.2; p = 0.006]). CONCLUSIONS: The sarcopenia index is a fair measure for muscle mass estimation among ICU patients and can modestly predict hospital and 90-day mortality among patients who do not have acute kidney injury at the time of measurement.
Keywords: Female; lidé středního věku; biologické markery; hodnoty glomerulární filtrace; Respiration, Artificial; hluboké zádové svaly; Tomography, X-Ray Computed; kreatinin; věkové faktory; umělé dýchání; kohortové studie; mužské pohlaví; Paraspinal Muscles; Retrospective Studies; retrospektivní studie; Humans; Cystatin C; cystatin C; Sarcopenia; lidé; Middle Aged; Intensive Care Units; mortalita v nemocnicích; počítačová rentgenová tomografie; Glomerular Filtration Rate; Cohort Studies; senioři; jednotky intenzivní péče; Age Factors; ženské pohlaví; Hospital Mortality; Aged; Creatinine; Biomarkers; Male; sarkopenie